2022
DOI: 10.3390/jmmp6040072
|View full text |Cite
|
Sign up to set email alerts
|

Laser Additive Manufacturing of Duplex Stainless Steel via Powder Mixture

Abstract: Laser additively manufactured duplex stainless steels contain mostly ferrite in the as-built parts due to rapid solidification of the printed layers. To achieve duplex microstructures (ferrite and austenite in roughly equal proportions) and, thus, a good combination of mechanical properties and corrosion resistance, an austenitic stainless steel powder (X2CrNiMo17-12-2) and a super duplex stainless steel powder (X2CrNiMoN25-7-4) were mixed in different proportions and the powder mixtures were processed via PBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In other studies, the authors developed new alloys, suitable for LPBF, by the dry mixing of elemental powders and/or pre-alloyed powders, allowing them to create custom duplex and super duplex powder blends with tailored chemical compositions. The aim was to promote austenite formation in the as-built condition [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, the authors developed new alloys, suitable for LPBF, by the dry mixing of elemental powders and/or pre-alloyed powders, allowing them to create custom duplex and super duplex powder blends with tailored chemical compositions. The aim was to promote austenite formation in the as-built condition [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Microcrystalline grain boundary austenite (GBA) was observed at the grain boundaries, exhibiting an allotriomorphic shape and morphology ( Figure 4 b). LPBF-related studies [ 5 , 6 , 7 , 8 , 9 , 11 , 12 , 14 , 21 , 28 , 29 ] have reported that extremely high cooling rates inhibit the formation of sigma phase in as-printed conditions. Additionally, an excess of nitrogen saturation within the ferrite matrix has been found to induce the formation of chromium nitride precipitates due to the formation of Cr-rich regions at grain boundaries (GB).…”
Section: Resultsmentioning
confidence: 99%
“…In the background of additive manufacturing, there is a growing interest also in DSS [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. This is evidenced by the development of Super-DSS grade 2507 (EN 1.4410) powder, which is specifically designed for additive manufacturing processes.…”
Section: Introductionmentioning
confidence: 99%
“…The austenitic and ferritic-austenitic microstructures can be produced via the partial substitution of Ni by Mn [17] or the mixture of austenitic stainless steel powders and super duplex stainless steel powders in different proportions. [18] The printing pores, microstructure, mechanical properties, and corrosion resistance were characterized in the previous studies. [13,17] It was found that the introduction of nitrogen tends to increase porosity due to the limited solubility of nitrogen in the steel matrix.…”
Section: Introductionmentioning
confidence: 99%